The Foam Cell Formation Associated With Imbalanced Cholesterol Homeostasis Due to Airborne Magnetite Nanoparticles Exposure. (1st August 2022) - Yu, Haiyi; Xu, Liting; Cui, Tenglong; Wang, Yu; Wang, Baoqiang; Zhang, Ze; Su, Ruijun; Zhang, Jingxu; Zhang, Rong; Wei, Yanhong; Li, Daochuan; Jin, Xiaoting; et al.
Abstract: Fine particulate matter (PM) is a leading environmental cause for the increased morbidity and mortality of atherosclerosis (AS) worldwide, but little is known about the toxic component and disturbance of PM exposure on foam cell formation, a crucial pathological process in AS. Airborne magnetite nanoparticles (NPs) have been reported to be detected in human serum, which inevitably encounter with macrophages in atherosclerotic plaques, thus throwing potential disturbance on the formation of macrophage-derived foam cells. Here we comprehensively unveiled that the environmental concentrations of PM exposure triggered and potentiated the formation of macrophage-derived foam cells using both real-ambient PM-exposed mice and AS mice models, including high-fat diet-fed mice and apolipoprotein E-deficient mice. The in vitro model further defined the dose-dependent response of PM treatment on foam cell formation. Interestingly, airborne magnetite NPs rather than nonmagnetic NPs at the same concentration were demonstrated to be the key toxic component of PM in the promoted foam cell formation. Furthermore, magnetite NPs exposure led to abnormal cholesterol accumulation in macrophages, which was attributed to the attenuation of cholesterol efflux and enhancement of lipoprotein uptake, but independent of cholesterol esterification. The in-depth data revealed that magnetite NPs accelerated the protein ubiquitination and subsequent degradation of SR-B1, a crucial transporter of cholesterol efflux. Collectively, these findings for the first time identified magnetite NPs as one key toxic component of PM-promoted foam cell formation, and provided new insight of abnormal cholesterol metabolism into the pathogenesis of PM-induced AS.